Demographic Gaps in Some Latin American Countries (1985-2020) - Sacco, Giuseppina; Sacco, Pietro (European Scientific Journal, ESJ, 2020)
Latin America, in general, is a great geographic, social, political, economic and cultural mosaic and, especially in the demographic field, is far from being a homogeneous aggregate. There have always been, and there are still today, differences between the various countries belonging to this geographical area, both in the ways in which the demographic phenomena have evolved and, mainly, in the times the different steps took for the evolutionary process regarding each of them. This paper will try to monitor the demographic evolution of the countries examined 1 in the period between the five-year periods 1985-1990 and 2015-2020. In addition, it will identify the possible existence of groupings of countries, similar within them and heterogeneous among them, through the cluster analysis technique, thus highlighting some explanatory indicators that have allowed the above mentioned evolution. The results obtained have led to think that it is necessary to study the economic, social, cultural and institutional aspects of every population, thus being able to cope with differential studies on the mortality and fertility of any population in order to interpret demographic phenomena.